Intrinsic tet(L) sub-class in Bacillus velezensis and Bacillus amyloliquefaciens is associated with a reduced susceptibility toward tetracycline - Nøhr-Meldgaard, Katrine; Struve, Carsten; Ingmer, Hanne; Agersø, Yvonne (Frontiers in Microbiology, 2022)
Annotations of non-pathogenic bacterial genomes commonly reveal putative antibiotic resistance genes and the potential risks associated with such genes is challenging to assess. We have examined a putative tetracycline tet(L) gene (conferring low level tetracycline resistance), present in the majority of all publicly available genomes of the industrially important operational group Bacillus amyloliquefaciens including the species B. amyloliquefaciens, Bacillus siamensis and Bacillus velezensis. The aim was to examine the risk of transfer of the putative tet(L) in operational group B. amyloliquefaciens through phylogenetic and genomic position analysis. These analyses furthermore included tet(L) genes encoded by transferable plasmids and other Gram-positive and -negative bacteria, including Bacillus subtilis. Through phylogenetic analysis, we could group chromosomally and plasmid-encoded tet(L) genes into four phylogenetic clades. The chromosomally encoded putative tet(L) from operational group B. amyloliquefaciens formed a separate phylogenetic clade; was positioned in the same genomic region in the three species; was not flanked by mobile genetic elements and was not found in any other bacterial species suggesting that the gene has been present in a common ancestor before species differentiation and is intrinsic. Therefore the gene is not considered a safety concern, and the risk of transfer to and expression of resistance in other non-related species is considered negligible. We suggest a subgrouping of the tet(L) class into four groups (tet(L)1.1, tet(L)1.2 and tet(L)2.1, tet(L)2.2), corresponding with the phylogenetic grouping and tet(L) from operational group B. amyloliquefaciens referred to as tet(L)2.2. Phylogenetic analysis is a useful tool to correctly differentiate between intrinsic and acquired antibiotic resistance genes.